CLIL in Catalonia: learning through talk and interaction in secondary science classrooms - Kirsch, Jane (2016)
This mixed-methods study concerns the teaching of CLIL to students in mainstream secondary schools in Catalonia. English proficiency levels among school students remain persistently low throughout Spain compared to other European countries, despite policies to lower the age at which pupils start to learn English and increase the time they spend in lessons. Given the limited space in the curriculum in Catalonia, which already has the challenge of teaching two official languages, CLIL has increasingly been viewed as a solution to bolster English competence. This study therefore sets out to explore interaction and discourse in CLIL and L1 secondary science classrooms to find out how teachers were able to achieve their CLIL learning aims, while comparing teaching strategies and pupil participation in CLIL and L1 learning environments. Qualitative methods (questionnaires and interviews) were used to measure student and teacher perceptions of CLIL, while a combination of qualitative and quantitative measures were employed to analyse transcripts from 20 hours of recorded lessons. The results show that teachers used a greater range of tasks in the CLIL lessons to scaffold learning, engage students and encourage participation. Learning was more visual and hands on in the CLIL classrooms, whereas in the L1 lessons it could feature long stretches of teacher talk with few student-centred activities. However, student participation was low in the CLIL lessons. Students struggled to ask and answer questions in English, and teachers were unable, and often reluctant, to employ strategies to get students speaking, for example, through the use of ELT-style speaking activities. The research also revealed high rates of L1 use, both to communicate within the CLIL lessons and to teach entire lessons on the course. This reflects the teachers’ view that the science took precedence over language learning and that their aim was to teach the same amount and depth of science content in the CLIL lessons as they would expect to teach when using students’ L1.